Amniotic band syndrome: a rare entity to be encountered - Sinha, Sushma; Malik, Surya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Amniotic band syndrome(ABS) is a disruption sequence with a broad spectrum of clinical manifestations ranging from partial amputations to major craniofacial and limb body wall defects. The commonest abnormalities usually involve the limbs and can range from simple constriction rings to complete amputation occurring at various levels. This case report is about a new born female baby who was normally delivered and she presented with complete absence of metacarpals and phalanges of the left hand. All the other limbs were normal. This case report throws a light on the different diagnostic modalities which can be used to diagnose amniotic band syndrome. Therapy of ABS is mostly surgical, with an individual approach to every single case. Interdisciplinary consulting and work is very often needed.